A Follow-Up Study on The Promotion of The Governance Institute of Home Affair Library Through Instagram Media - Nursupian, Jajang (Indonesian Journal of Librarianship, 2022)
Background: This is a follow-up study from Rahmadanita, which established a general description regarding the ineffective operation of the promotions carried out by the IPDN (Governance Institute of Home Affairs) Library. Since the Covid-19 pandemic, this library has begun to focus on and intensively promote services through owned accounts on social media, including WA, Facebook, Youtube, and Instagram. Purpose: This study aims to determine the patterns by which promotion is carried out by the IPDN library through Instagram media. Method: A literature review method was implemented with a scientific interdisciplinary approach. Result: The results showed that the promotions carried out by the library on the marketing indicator included Product, Place, Promotion, People, Process, and Customer Service. Meanwhile, the promotion mix dimension indicated the achievement of followers' invitation to support library activities and be interested in reading programs. IPDN library posts also developed followers' awarenesses, update patterns, solicitation captions, and interactions. Conclusion: Despite the various shortcomings, the IPDN Library still effectively carried out promotions through Instagram. However, the formal appointment of an Instagram admin through a decree was very necessary for the IPDN millennial librarians, indicating the minimization of existing challenges. Keywords: Instagram; Social Media Administrator; Library Promotion; IPDN Library